PROBLEMS ENCOUNTERED BY FEMALE SCHOOL PRINCIPALS IN TURKEY - İhsan Topcu; Oksana Manolova Yalçin; Orhan Cingöz; Sare Akkaya (Istraživanja u Pedagogiji, 2024)
In this study, the problems faced by women principals in school administration were investigated. Phenomenology model was preferred in the study. The study group consisted of 17 female school principals working in public state schools in five central districts of Kayseri province. The data were collected through a semistructured interview form and analyzed by content analysis method. Research results show that half of female managers believe that they fulfill their managerial duties and meet their previous expectations. Also the same half of those female principals have gained power and status, and overcome the difficulties faced by while the other half have not met their expectations. Those others have experienced regret and disappointment due to the challenging conditions and inequality of opportunities for themselves. Main problems are listed as male principals' gender discrimination, underestimation of women, lack of recognition of women's success and injustice in work distribution. It is found that the majority of the participants do not have problems with teachers and students. Yet, some female principals had problems with female teachers due to jealousy, envy and exclusion, and some of them had problems with male teachers due to gender-based prejudice and not accepting women as principals. The study showed that the majority of participants had problems with male parents and that the problem stemmed from the prejudice that women cannot be principals. It is seen that the majority of the participants do not have problems with the provincial and district national education directorates and the staff of other schools during the school management process. Regarding career planning, it was stated that the majority of the participants had plans to continue and advance in their current positions. It is seen that some female school administrators want to leave the school administration due to reasons such as long working hours, heavy responsibility, stress factor, concern about neglecting family and home responsibilities, loneliness and exclusion due to their position at the school.